Psychological Impact of Air Pollution on Undergraduate Students of Lahore Pakistan - Saima Majeed, Humna Waqar, Salman Awan, Zain Ul Abidin, Eesha Sohail, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Air pollution has become one of the most prevalent health issues in the entire world. Smog is defined as the fog that is intensified or contaminated by smoke. Psychological distress is the emotional or mental discomfort that can lead to anxiety, stress, and other mental problems. Aim: To evaluate the relationship between psychological distress and air pollution in undergraduate students of Lahore. Study design: Cross Sectional study. Methodology: The sample size (n=194) was calculated with G power analysis. A web-based survey was conducted, and the data was collected from 200 students in the age range of 18 to 25 (M=21.39, SD=1.23) from both public and private universities. Data was evaluated by using SPSS version 24. Pearson’s correlation was applied. Results: Results indicated that air pollution and psychological distress are positively correlated r=.981, N=200, p < .01. Air pollution is associated with psychological distress. Conclusion: It was concluded that air pollution perception is positively correlated to Perceived psychological distress. Thus better their perception regarding air pollution the more they are having psychological distress. Keywords: Air Pollution, Psychological Impact, Psychological Distress and Undergraduate Students.